#### Answer

x = 0.7916666667

#### Work Step by Step

Simplifying
2.3x + -4.7 + 0.6(3x + 5) = 0.7(3 + -1x)
Reorder the terms:
2.3x + -4.7 + 0.6(5 + 3x) = 0.7(3 + -1x)
2.3x + -4.7 + (5 * 0.6 + 3x * 0.6) = 0.7(3 + -1x)
2.3x + -4.7 + (3 + 1.8x) = 0.7(3 + -1x)
Reorder the terms:
-4.7 + 3 + 2.3x + 1.8x = 0.7(3 + -1x)
Combine like terms: -4.7 + 3 = -1.7
-1.7 + 2.3x + 1.8x = 0.7(3 + -1x)
Combine like terms: 2.3x + 1.8x = 4.1x
-1.7 + 4.1x = 0.7(3 + -1x)
-1.7 + 4.1x = (3 * 0.7 + -1x * 0.7)
-1.7 + 4.1x = (2.1 + -0.7x)
Solving
-1.7 + 4.1x = 2.1 + -0.7x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '0.7x' to each side of the equation.
-1.7 + 4.1x + 0.7x = 2.1 + -0.7x + 0.7x
Combine like terms: 4.1x + 0.7x = 4.8x
-1.7 + 4.8x = 2.1 + -0.7x + 0.7x
Combine like terms: -0.7x + 0.7x = 0.0
-1.7 + 4.8x = 2.1 + 0.0
-1.7 + 4.8x = 2.1
Add '1.7' to each side of the equation.
-1.7 + 1.7 + 4.8x = 2.1 + 1.7
Combine like terms: -1.7 + 1.7 = 0.0
0.0 + 4.8x = 2.1 + 1.7
4.8x = 2.1 + 1.7
Combine like terms: 2.1 + 1.7 = 3.8
4.8x = 3.8
Divide each side by '4.8'.
x = 0.7916666667
Simplifying
x = 0.7916666667